VertiMax
VertiMax provides resisitance training that excites the neural pathways and allows permanent memeorization and explosive power enhancement to occur - even in just one session. Most conventional systems use two (or four) elastic bands tied to a platform surface (see yellow below left.) These designs cause resistance to increase exponentially because the short elastic bands go slack when squatting and are severely stretched when leaping. The primitive design disrupts balance and can not apply constant resistance which is required for muscle preceptors to confirm the memorization process required for maximizing explosive power development. VertiMax has four 13 foot cords that retract down through the platform and coil around 16 bearinged pulleys under the platform! This unique and patented capability is the main reason VertiMax produces amazing results quick. Special mechanical devices under the platform provide near-constant level of resistance from the squatted position all the way to the peak of the jump. This means there are no slack cords at the bottom and no "yank-back" at the top. But much more importantly, it is this unique and patented capability of VertiMax that excites the neural pathways and allows permanent memorization and explosive power enhancement to occur in just one session!